The girl in the letter - Gunnis, Emily (London : Headline Review, 2019)
In the winter of 1956 pregnant young Ivy is sent in disgrace to St Margaret's, a home for unmarried mothers in the south of England, to have her child. Her baby daughter is adopted. Ivy will never leave. Sixty years later, journalist Samantha stumbles upon a series of letters from Ivy to her lover, pleading with him to rescue her from St Margaret's before it is too late. keen that the truth should never be told?
Some copies include excerpt from The Lost Child.
Keywords: Unmarried mothers -- Fiction; Adoption -- Fiction; Journalists -- Great Britain -- Fiction; Historical fiction; Detective and mystery fiction